The Effect of Social Media to the Brand Awareness of a Product of a Company - Hansel Bagus Tritama; Riswan Efendi Tarigan (CommIT (Communication and Information Technology) Journal, 2016)
Social  media  is an online media, where the users can easily participate, share, and create any content such as banner,  posters, videos and advertisement.  Many companies  use these  social  media as  a tool to promote their products  and make  customers aware  with their brand. On the other hand, not all companies  succeed to market their products and make their products are at their customers’ awareness. The purpose of this research is to find the correlation  between social media commu- nication marketing  with companys brand awareness in social media.  The research  method for this research  is quantitative  research.  This method collects  data with explanative research type which explains the relationship between two variables. The result  of this research  is to show that marketing  communication in a company has an impact to company’s brand awareness. In addition, this research wants to show that marketing via social media can give impact  to company’s revenue. The summary of this research  is to get significant  information  about the effect of social media toward companys brand awareness through quantitative  and explanative  research  method due to the rising of social media.